Sustainable metamorphosis: examining sustainability transformation into value of financial institutions - Lapinskaitė, Indrė; Skvarciany, Viktorija (Journal of Business Economics and Management, 2023)
The relevance of sustainable development in the financial institution and its value is significant in today’s financial landscape. This research aims to evaluate the efficiency of converting sustainable development outcomes, quantified through ESG, into a financial institution’s valuation, measured by the P/E ratio. In order to reach the aim, the DEA method was applied. The results reveal that only one financial institution has an efficiency score of 1, signifying a notable efficiency level. Most financial institutions in the dataset possess efficiency scores (represented by theta) below 0.1, indicating a relative inefficiency in converting their E, S, and G scores into P/E ratios. The results reveal that high E, S, and G scores do not result in higher P/E ratios. It might be advisable to diversify investments across different financial institutions with diverse ESG profiles to mitigate risk and optimise returns. These potential research perspectives offer opportunities for a more profound understanding of the connection between ESG factors and the valuation of financial institutions. They allow for an examination of the quality and transparency of ESG reporting, considering the specific internal factors relevant to international financial institutions, as ESG continues to gain recognition as an integral component of a company’s intangible assets. First published online 04 January 2024